2021
DOI: 10.1093/g3journal/jkab374
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Drosophila melanogaster Hox gene Ultrabithorax is not overtly regulated by the intronic long noncoding RNA lncRNA:PS4 in a wild-type genetic background

Abstract: Long non-coding RNAs (lncRNAs) have been implicated in a variety of processes in development, differentiation, and disease. In Drosophila melanogaster, the bithorax Hox cluster (BX-C) contains three Hox genes (Ultrabithorax (Ubx), abdominal-A (abd-A), and Abdominal-B (Abd-B)), along with a number of lncRNAs, most with unknown functions. Here, we investigated the function of a long non-coding RNA, lncRNA: PS4 that originates in the second intron of Ubx and is transcribed in the antisense orientation to Ubx. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Of note, a systematic in-situ hybridization survey ( Pease et al, 2013 ) showed that Drosophila embryos express an antisense transcript in its 5’ region ( lncRNA:bxd ), as well as within its first intron ( lncRNA:PS4 ). It is thought that Drosophila bxd regulates Ubx , possibly by transcriptional interference or by facilitation of the Fub-1 boundary effect ( Petruk et al, 2006 ; Ibragimov et al, 2023 ), while the possible regulatory roles of PS4 remain debated ( Hermann et al, 2022 ). While these dipteran non-coding transcripts lack detectable sequence similarity with the lepidopteran IT1 and AS5’ transcripts, further comparative genomics analyses of the Ubx region across the holometabolan insect phylogeny should clarify the extent to which Hox cluster lncRNAs have been conserved or independently evolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a systematic in-situ hybridization survey ( Pease et al, 2013 ) showed that Drosophila embryos express an antisense transcript in its 5’ region ( lncRNA:bxd ), as well as within its first intron ( lncRNA:PS4 ). It is thought that Drosophila bxd regulates Ubx , possibly by transcriptional interference or by facilitation of the Fub-1 boundary effect ( Petruk et al, 2006 ; Ibragimov et al, 2023 ), while the possible regulatory roles of PS4 remain debated ( Hermann et al, 2022 ). While these dipteran non-coding transcripts lack detectable sequence similarity with the lepidopteran IT1 and AS5’ transcripts, further comparative genomics analyses of the Ubx region across the holometabolan insect phylogeny should clarify the extent to which Hox cluster lncRNAs have been conserved or independently evolved.…”
Section: Discussionmentioning
confidence: 99%
“…Fub-1/bxd long non-coding RNAs (lncRNAs) situated 5’ of Ubx are thought to participate in Ubx regulation in the PS5 (posterior T3 to anterior A1) parasegment ( Petruk et al, 2006 ; Ibragimov et al, 2023 ). An intronic lncRNA dubbed lncRNA:PS4 is expressed in the PS4 parasegment (posterior T2 - anterior T3), and appears to stabilize Ubx in this region in mutant contexts ( Hermann et al, 2022 ). Little is known about how insect Hox genes are regulated outside of Drosophila , where they co-localize into a single Hox cluster, and where Antp and Ubx thus occur in contiguous positions ( Gaunt, 2022 ; Mulhair and Holland, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a systematic in-situ hybridization survey (Pease et al 2013) showed that Drosophila embryos express an antisense transcript in its 5’ region ( lncRNA:bxd ), as well as within its first intron ( lncRNA:PS4 ). It is thought that Drosophila bxd regulates Ubx , possibly by transcriptional interference or by facilitation of the Fub-1 boundary effect (Petruk et al 2006; Ibragimov et al 2023), while the possible regulatory roles of PS4 remain debated (Hermann et al 2022). While these dipteran non-coding transcripts lack detectable sequence similarity with the lepidopteran IT1 and AS5’ transcripts, further comparative genomics analyses of the Ubx region across the holometabolan insect phylogeny should clarify the extent to which Hox cluster lncRNAs have been conserved or independently evolved.…”
Section: Discussionmentioning
confidence: 99%
“…Fub-1/bxd long non-coding RNAs (lncRNAs) situated 5’ of Ubx are thought to participate in Ubx regulation in the PS5 (posterior T3 to anterior A1) parasegment (Petruk et al 2006; Ibragimov et al 2023). An intronic lncRNA dubbed lncRNA:PS4 is expressed in the PS4 parasegment (posterior T2 - anterior T3), and appears to stabilize Ubx in this region in mutant contexts (Hermann et al 2022). Little is known about how insect Hox genes are regulated outside of Drosophila , where they co-localize into a single Hox cluster, and where Antp and Ubx thus occur in contiguous positions (Gaunt 2022; Mulhair and Holland 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrabithorax ( Ubx ), Abdominal-A ( Abd-A ), and Abdominal-B ( Abd-B ) are known for the spatiotemporal expression pattern in development and its mutants will have disrupted abdominal segments [ 127 ]. However, for lncRNA:PS4 , despite having the same expression profile as Ubx , promoter deletion in the lncRNA:PS4 mutant shows no direct expression difference in Ubx [ 140 ]. Another lncRNA, acal , is shown to be responsible for dorsal closure through the JNK signalling pathway, and mutations in acal are lethal [ 128 ].…”
Section: Lncrna In Drosophilamentioning
confidence: 99%